TEACHING ENGLISH THROUGH LITERATURE - Donny Syofyan (Indonesian JELT, 2012)
Teaching English in Indonesia, particularly for students, remains agreat challenge owing to the fact that English is a foreign languagein this country. The challenge could be tackled through teachingliterature. Literature has been a subject of study in many countriesat a secondary or tertiary level, but until recently has not been givenmuch emphasis in the EFL/ESL classroom. It is considered a veryversatile subject and is generally considered one of the most difficult subjects to teach. Central to teaching literature in the classroom is to let students be involved in the experience and let them observe life more closely.Keywords: Teaching English in Indonesia, teaching literature